The effectiveness of organic fertilizers of chicken, cow and sheep manure against the growth of cabbage, caisim, chicory plants vegetatively - Ahmad Zamzami; Rev. Puri I. W; Angga Jawi A; Herlinda Putri U; Desy Cahya W (Proceeding International Conference on Religion, Science and Education, 2023)
Flower cabbage (Brassica oleracea var. botrytis, L), caisim (Brassica juncea L), and chicory (Brassica pekinensis L) are types of vegetable plants with high public interest due to their good nutrition at a price economical. Fertilizer application is an important factor that can determine the productivity and quality of the crops produced. The purpose of the review is to collect information about the effect of organic fertilizers from chicken, cow and sheep manure on cabbage, caisim and chicory plants vegetatively. The writing method is carried out through the study of literature sourced from books, journals, proceedings, website and news portals. Based on the observed data, it was found that organic food can use chicken, beef and sheep manure as an ingredient for its manufacture. The composition of organic fertilizer content with manure material consists of macro nutrients such as Mg, S, Ca, N, P, K and micronutrients such as Zn, Mo, Cu, Co, B, Fe, and Mn. Application of organic fertilizer chicken and goat manure on cabbage, caisim, and chicory plants shows an influence on plant height and the number of leaves differs according to the dose of administration but the use of cow dung does not show a noticeable difference. The application of organic fertilizer for chicken and goat manure also has a noticeable effect on the wet weight and dry weight of plants with the best response, namely chicken manure. This condition is influenced by differences in the nutrient content in manure such as C-organic, Nitrogen, C/N Ratio, phosphorus, Potassium, and Water Content. The C-organic, Nitrogen, and Potassium content of goat manure has the highest value. While the highest phosphorus content, water content and C / N ratio are in chicken and cow manure. These ingredients are very important for plants including as a source of energy for microorganisms, stimulating plant vegetative growth, stimulating the formation of plant parts, the formation of proteins and carbohydrates, and as antibodies for plants. The conclusion of the review is that the use of organic fertilizers for chicken and goat manure affects the vegetative of plants, but the organic fertilizer of cow dung does not differ markedly from the vegetative growth of plants.